1990
DOI: 10.1007/bf00137327
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome polymorphism due to pericentric inversion in Zonotrichia capensis (Emberizidae-Passeriformes-Aves)

Abstract: Chromosomal polymorphism involving chromosome pairs 3 and 5 problably due to a pericentric inversion is reported for 60 specimens of Zonotrichia capensis (Passeriformes-Aves). The frequency of seven different karyotypes, due to the fact that chromosome 3 is present in the 3 s' and 3 sm conditions and chromosome 5 in the 5 st and 5 m conditions, and the significance of this polymorphism are discussed for the genus Zonotrichia and for other genera from the same family (Emberizidae).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Another possibility is that ZAL2 m may have been introduced into the white-throated sparrow population by hybridization with another species. Indeed, shared chromosomal polymorphisms are present within the Junco genus (Shields 1973), possibly on chromosome 2 (but see Rocha et al 1990), and matings between Z. albicollis and J. hyemalis have been reported (Dickerman 1961). However, our sequence analysis showed that the ZAL2 and ZAL2 m chromosomes share a much more recent common ancestor with each other than either does with J. hyemalis, making hybridization with that species an unlikely source for ZAL2 m .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Another possibility is that ZAL2 m may have been introduced into the white-throated sparrow population by hybridization with another species. Indeed, shared chromosomal polymorphisms are present within the Junco genus (Shields 1973), possibly on chromosome 2 (but see Rocha et al 1990), and matings between Z. albicollis and J. hyemalis have been reported (Dickerman 1961). However, our sequence analysis showed that the ZAL2 and ZAL2 m chromosomes share a much more recent common ancestor with each other than either does with J. hyemalis, making hybridization with that species an unlikely source for ZAL2 m .…”
Section: Discussionmentioning
confidence: 67%
“…However, from comparative studies in other Zonotrichia sparrows it was inferred that ZAL2 was likely the ancestral arrangement and that ZAL2 m was not a shared polymorphism, but instead arose exclusively in the white-throated sparrow lineage (Thorneycroft 1975). Although chromosomal polymorphisms have subsequently been detected in another bird in this genus, Z. capensis (Rocha et al 1990), they are distinct from ZAL2 m . The lack of evidence for ZAL2 m in other Zonotrichia sparrows may reflect insufficient sampling or that this arrangement was present in an ancestral population but retained only in the whitethroated sparrow.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative analyses between the white-throated sparrow and its relatives can be quite revealing about genomic evolution. In the rufous-collared sparrow ( Zonotrichia capensis ), Rocha et al [ 64 ] reported polymorphisms in chromosomes 3 and 5 – also presumably due to pericentric inversions. The closely related junco exhibits polymorphisms for pericentric inversions in chromosomes 2 and 5 [ 65 ] and the white-crowned sparrow ( Z. leucophrys ) has centric rearrangements in chromosomes 3, 5, and 12 [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…capensis have shown that this species has 80 chromosomes ( de Lucca, 1974 ; de Lucca and Rocha, 1985 ). Polymorphisms involving two autosomal pairs were also identified, probably due to intrachromosomal rearrangements, such as inversions ( de Lucca and Rocha, 1985 ; Rocha et al , 1990 ). The polymorphisms described for Z .…”
Section: Introductionmentioning
confidence: 99%
“…capensis occur in autosomal pairs 2 and 4. Pair 2 can be acrocentric or submetacentric (2 A and 2 Sm ), while pair 4 can be acrocentric or metacentric (4 A and 4 M ) ( de Lucca and Rocha, 1985 ; Rocha et al , 1990 ). The presence of these two polymorphic pairs, with the occurrence of four chromosomal forms, allows the combination of nine different cytotypes.…”
Section: Introductionmentioning
confidence: 99%